2016
DOI: 10.1002/jbio.201500336
|View full text |Cite
|
Sign up to set email alerts
|

Repeated transcranial low‐level laser therapy for traumatic brain injury in mice: biphasic dose response and long‐term treatment outcome

Abstract: We previously showed that near-infrared laser photobiomodulation (PBM) (810 nm, CW, 18 J/cm2, 25 mW/cm2) delivered to the mouse daily for 3-days after a controlled cortical impact traumatic brain injury (TBI) gave a significant improvement in neurological/cognitive function. However the same parameters delivered 14X daily gave significantly less benefit. This biphasic dose response intrigued us, and we decided to follow the mice that received 3X or 14X laser treatments out to 56-days post-TBI. We found the 14X… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
40
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(43 citation statements)
references
References 51 publications
(79 reference statements)
0
40
0
3
Order By: Relevance
“…Intriguingly, the beneficial effects of NIR PBM follow a biphasic dose-response curve which adheres closely to the Arndt-Schulz principle (Huang et al, 2009;Sharma et al, 2011;Xuan et al, 2016). At very low doses of stimulation, the effects of PBM are negligible.…”
Section: Cytochrome C 2+mentioning
confidence: 60%
“…Intriguingly, the beneficial effects of NIR PBM follow a biphasic dose-response curve which adheres closely to the Arndt-Schulz principle (Huang et al, 2009;Sharma et al, 2011;Xuan et al, 2016). At very low doses of stimulation, the effects of PBM are negligible.…”
Section: Cytochrome C 2+mentioning
confidence: 60%
“…Additionally, GFAP levels increase when cerebral tissues are damaged due to trauma (52). GFAP is an early diagnostic indicator of TBI and a sensitive indicator of mortality following TBI (53). GFAP is further the major protein of glial intermediate filaments in astrocytes and is often used as a hallmark of astrocyte reactivity (54).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, researchers have shifted the focus of research to the application of LLLT on brain disorders [1][2][3]. During the past decade, LLLT has been widely used to study neurological and psychological diseases [3] such as depressionlike behaviors [4][5][6][7][8], Alzheimer's disease (AD) [9][10][11][12][13][14][15][16][17][18][19][20], Parkinson's disease [21], stroke [22,23] and traumatic brain injury (TBI) [24][25][26][27][28][29][30][31][32]. Because red or NIR light can effectively penetrate into brain tissues [33,34], it can be noninvasive and play a beneficial role in increasing ATP biosynthesis and neurogenesis [1,2].…”
Section: Introductionmentioning
confidence: 99%
“…Transcranial LLLT improved neuromuscular performance, increased brain derived neurotrophic factor (BDNF), reduced brain lesion volume, enhanced learning and memory, and overall improved the neurological severity score in mouse model of TBI [24,25,[28][29][30][31][32]. In addition, the clinical studies found that LLLT could improve cognition and decrease depression, anxiety, headache and insomnia in patients with chronic Review Xiang-Ping Chu and long-term spatial and recognition memory impairments in rats that were injected bilaterally with Aβ 1-42 to the hippocampus CA1 region [9].…”
Section: Introductionmentioning
confidence: 99%